Chemical analysis of the human brain by imaging mass spectrometry. Issue 18 (19th August 2021) - Ajith, Akhila; Sthanikam, Yeswanth; Banerjee, Shibdas
Abstract : Imaging mass spectrometry enables visualization of the neuroanatomical distribution of thousands of biochemicals in the human brain, providing a wealth of information for diagnostic, prognostic, and therapeutic developments for neuro diseases. Abstract : Analysis of the chemical makeup of the brain enables a deeper understanding of several neurological processes. Molecular imaging that deciphers the spatial distribution of neurochemicals with high specificity and sensitivity is an exciting avenue in this aspect. The past two decades have witnessed a significant surge of mass spectrometry imaging (MSI) that can simultaneously map the distribution of hundreds to thousands of biomolecules in the tissue specimen at a fairly high resolution, which is otherwise beyond the scope of other molecular imaging techniques. In this review, we have documented the evolution of MSI technologies in imaging the anatomical distribution of neurochemicals in the human brain in the context of several neuro diseases. This review also addresses the potential of MSI to be a next-generation molecular imaging technique with its promising applications in neuropathology.